PENERAPAN MEDIA PEMBELAJARAN ETNOMATEMATIKA GOMO TOMA “CONGKLAK” UNTUK MATERIOPERASI BILANGAN BULAT PADA SISWA KELAS VII SMPK ALVAREZ PAGA TAHUN PELAJARAN 2018/2019 - Wilfrida M.M.D.S. Seko (Program Studi Pendidikan Matematika, 2020)
Based on the results of interviews with the mathematics teachers of class VII SMPK Alvarez Paga Academic year 2018/2019 found that students mastery and learning outcomes in integer material is relatively low. This is because teachers still use convetional methods. As a teacher should be able to apply varied learning models and one of them is to use learning media. In this research used the gomo toma “congklak” ethnomatematics learning media in order for students to aperate integers. This research is experimental research and used a quantitative approach. The population in this study were all VII grade students of SMPK Alvarez Paga, andthe sample wasclass VII B. The data analysis technique used is covariance analysis. The results of the study showed that the application Gomo Toma “congklak” learning media for integer operating material resulted in learning devices that were well qualified (validity, reliability, sensitivity). The results of the covariance analysis obtained a statistical value Fhitung = 8.44 > Ftabel = 4.21 with the numerator dk = 1 and the denominator = 27, giving a significant value. This shows that the application of gomo toma “congklak” learning media can improve the learning outcomes of class VIIB students of SMPK Alvarez Paga in the Academic Year 2018/2019`